Uniqueness of infrared asymptotics in Landau gauge Yang-Mills theory: II. - Fischer, Christian S.; Pawlowski, Jan M. (Physical review. D, Particles, fields, gravitation, and cosmology, 2009)
We present a shortened and simplified version of our proof [C. S. Fischer and J. M. Pawlowski, Phys. Rev. D 75, 025012 (2007).] of the uniqueness of the scaling solution for the infrared asymptotics of Green functions in Landau gauge Yang-Mills theory. The simplification relates to a new renormalization group-invariant arrangement of Green functions applicable to general theories. As before the proof relies on the necessary consistency between Dyson-Schwinger equations and functional renormalization group equations. We also demonstrate the existence of a specific scaling solution for both, Dyson-Schwinger equations and functional renormalization group equations, that displays uniform and soft kinematic singularities.
Gesehen am 05.12.2017